EDMODO VIRTUAL LEARNING ENVIRONMENTS IN TEACHING ENGLISH - Aji, Mahendra Puji Permana (English Education:Journal of English Teaching and Research, 2016)
In recent years, the integration of Information and Communication Technology (ICT), especially the internet, in teaching and learning process becomes an essential part of the teachers’ duties. As a teacher, we should be able to integrate the internet in teaching and learning process and purpose of this new medium as potential source to our students to improve their English competence. One of the internet facilities is Edmodo. It refers to as with any social network, can be used as a place to post and critique work, facilitate collaboration, and post creative material for an audience. The activities are not only focused on the students and teacher, but also the parents too. Parents can also view this Edmodo, either under their child's username or they may create their own account. Drawing from author’s experience in integrating Edmodo into his class for first and third year’s students of English Study Program, University of Nusantara PGRI Kediri, this paper attempts to demonstrate some potential uses of Edmodo in teaching learning process. Some pedagogical implications are further discussed. Using these Edmodo,it is expected that students will develop their English skills as well as have a lot of fun.